Effects of a single nucleotide polymorphism in the leptin gene on the productive traits of dairy buffaloes (Bubalus bubalis) - Zetouni, Larissa [UNESP]; De Camargo, Gregório Miguel Ferreira [UNESP]; Da Silva Fonseca, Patrícia Dias [UNESP]; Gil, Fernanda Maria Monsalves [UNESP]; Lugo, Naudin Alejandro Hurtado [UNESP]; Aspilcueta-Borquis, Rusbel Raul [UNESP]; Cervini, Marcelo; Tonhati, Humberto [UNESP] (Springer Nature, 2013)
The gene responsible for coding the leptin hormone has been associated with productive and reproductive traits in cattle. In dairy cattle, different polymorphisms found in the leptin gene have been associated with several traits of economic interest, such as energy balance, milk yield and composition, live weight, fertility and dry matter consumption. The aim of this study was to detect genetic variability in the leptin gene of buffaloes and to test possible associations with milk yield, fat and protein percentages, age at first calving and first calving interval. Three genotypes (AA, AG and GG) were identified by polymerase chain reaction-restriction fragment length polymorphism, which presented genotypic frequencies of 0.30, 0.54 and 0.16, respectively. The allele frequencies were 0.57 for the A allele and 0.43 for the G allele. No significant effects were found in the present study, but there is an indicative that leptin gene affects lipid metabolism. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Bubalus bubalis; Leptin; Polymorphism; SNP; leptin; female; gene; gene frequency; genetic variability; genotype; gestational age; lactation; leptin gene; lipid metabolism; milk yield; nonhuman; nucleotide sequence; polymerase chain reaction; protein metabolism; reproduction; restriction fragment length polymorphism; single nucleotide polymorphism; water buffalo; Bos; Bubalus